(Dé)classer la “médecine populaire” en Suisse: de la suspicion de charlatanisme à la reconnaissance patrimoniale - Julie Perrin (Anthropologie & Santé)
By characterizing the Intangible Cultural Heritage (ICH) as a "mainspring of cultural diversity," UNESCO has demonstrated its will to recognize marginalized cultural practices. However, the identification process conducted by the countries involved in the framework of the 2003 Convention tends to exclude certain ICH expressions. In the context of its Swiss implementation, this study explores the heritagization of practices related to "folk medicine". Drawing on an ethnographic approach, it accounts for the socio-historical trajectory of this category and the way heritage making involves diverse adjustments of these practices. Practices are thus adjusted and adapted to international standards and incorporated in hegemonic cultural representations. The study concludes that the requalification of these practices in a heritage logic takes into consideration the formal health system and reproduces medical hierarchies.